Literature Survey on Compact Microstrip Patch Antennas for Wireless Application - Kanniga, E.; Sindhuja, S. (International Journal of Psychosocial Rehabilitation, 2019)
The increasing growth of wireless system requires miniaturized antenna.Truly isotropic antennas do not exist. The most straight forward adaptive solution is to propose an antenna radiating as stable as possible in all directions. Recently antennas with quasi isotropic coverage are of increasing interest for researchers. Microstrip patch array antenna for X-band application is to be designed using any EDA Tool (ADS or HFSS). Miniaturization is possible and we just have to maintain minimum of 0.3mm line width for fabrication of the antenna. Metamaterial based miniaturization needs to be realized once the substrate is identified accordingly.